PENGARUH SALES PROMOTION DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ECOQUA PADA PT AIR GANGGA DEWATA ALAMI KABUPATEN GIANYAR - Iga Jaya Aditya, Dewa Gede; Sumerta, I Komang (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
The use of the advertising idea for a agency can aid the achievement of the enterprise being done. One of the advertising techniques to fulfill the extraordinary wishes of the goal institution of consumers is income advertising and product best. Sales advertising and product best are designed to stimulate wonderful emotional responses from customers as an attempt to enhance purchaser shopping choices. The motive of this take a look at become to decide the impact of income advertising and product best on shopping choices at PT Air Gangga Dewata Alami. Determination of the wide variety of samples become done the use of the Cochran Formula in order that the wide variety of samples become set at 96. The sampling approach used become purposive sampling with the aid of using specifying positive criteria. Primary information series become done the use of a questionnaire. To get solutions to the proposed hypothesis, the information evaluation approach used is a couple of linear regression. Based at the consequences of the evaluation that has been done, it may be concluded: (1) income advertising and product best have a wonderful and extensive impact on shopping choices, (2) income advertising has a wonderful and extensive impact on shopping choices, (3) product best has a wonderful and extensive impact on choices purchase. Advice that may be given to enhance shopping choices is that PT Air Gangga Dewata Alami is greater energetic and energetic in sporting out advertising activities, designing product packaging this is complete of shadeation in order that it's miles greater appealing and retaining and enhancing the best of Ecoqua each in phrases of merchandise and services